Moral fictionalism - Kalderon, Mark Eli, 1964- (Oxford : Clarendon, 2005)
This book argues that morality is a fiction by means of which emotional attitudes are conveyed. Kalderon's fictionalism shows that non-cognitivism can manage without controversial semantics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ethics; Philosophy